2023
DOI: 10.1002/pi.6495
|View full text |Cite
|
Sign up to set email alerts
|

Plasticizing effect of 1‐butyl‐3‐methylimidazolium bromide content on poly(vinyl alcohol)

Abstract: PVA/IL composites were successfully prepared with an ionic liquid (IL), 1‐butyl‐3‐methylimidazolium bromide and poly(vinyl alcohol) (PVA). The plasticizing effect of IL on PVA was investigated using Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), X‐ray diffraction (XRD), thermogravimetric analysis (TGA) and melt flow index (MI) measurements. FTIR analysis indicated that the anion (Br−) of IL could form hydrogen bonds with the hydroxyl groups of PVA. With an increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In addition, the broad peak of OH in DB shifted to higher wavenumbers, which indicated that hydroxyl groups of DM could form intermolecular H-bonds with anions (Br À ) of BMIMBr. [20] In Figure 1b, the characteristic absorption peak for PVA at the wave number of 3269 cm À 1 was ascribed to the stretching vibration of OH. The peaks at 2938 cm À 1 and 2906 cm À 1 were attributed to CH 2 asymmetric and symmetric stretching vibration.…”
Section: Interactions Between Pva and Dbmentioning
confidence: 96%
See 4 more Smart Citations
“…In addition, the broad peak of OH in DB shifted to higher wavenumbers, which indicated that hydroxyl groups of DM could form intermolecular H-bonds with anions (Br À ) of BMIMBr. [20] In Figure 1b, the characteristic absorption peak for PVA at the wave number of 3269 cm À 1 was ascribed to the stretching vibration of OH. The peaks at 2938 cm À 1 and 2906 cm À 1 were attributed to CH 2 asymmetric and symmetric stretching vibration.…”
Section: Interactions Between Pva and Dbmentioning
confidence: 96%
“…This was because the reason was same as the T m2 , which destroyed original hydrogen bond interactions of PVA and retarded the crystallization process of PVA. [20] With the increase of DB, the above destructive effect become more and more obvious, which resulted in a decrease in T c1 value. With the further increase of DB (� 30 wt%), there were two crystallization peaks in PVA/DB composites.…”
Section: Thermodynamic Properties Of Pva/db Compositesmentioning
confidence: 99%
See 3 more Smart Citations